Bioaccumulation of Microcystins In Lettuce - Hereman, Talita Caroline [UNESP]; Bittencourt-Oliveira, Maria do Carmo [UNESP] (Wiley-Blackwell, 2012)
The contamination of lettuce (Lactuca sativa L.) by water-borne crude extracts of the cyanobacterium microcystin-producing Microcystis aeruginosa (Kutzing) Kutzing was investigated. The aim of the study was to determine whether bioaccumulation of microcystins occurs in lettuce foliar tissue when sprayed with solutions containing microcystins at concentrations observed in aquatic systems (0.62 to 12.5 mu g center dot L-1). Microcystins were found in lettuce foliar tissues (8.31 to 177.8 mu g per Kg of fresh weight) at all concentrations of crude extracts. Spraying with water containing microcystins and cyanobacteria may contaminate lettuce at levels higher than the daily intake of microcystins recommended by the World Health Organization (WHO), underscoring the need to monitor such food exposure pathways by public authorities.
Keywords: alimentary security; cyanobacteria; food contamination; irrigation; Microcystis aeruginosa; vegetables